Application of music therapy in college student athletes' mental health education - Yuchuan Rong , (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
This study aims to investigate music therapy's effect on college athletes' mental health education. This study used a randomized controlled experimental method to recruit 49 college badminton participants for intervention. Before the intervention, all participants were randomly assigned to two groups: the mindfulness group (n = 25) or the control group (n = 24). They received a seven-week course in music. The athletes in the control group received no intervention. After completing MAIC training, the mindfulness group college athletes dramatically outperformed the control group college athletes in mindfulness, anxiety, sadness, training satisfaction, and competition acceptance. There were statistically significant differences (P < 0.01) between groups in the mindfulness, anxiety, training, Competition Satisfaction, and acceptance categories. Only mindfulness, anxiety, training, Competition Satisfaction, and acceptance characteristics differed significantly between groups (P 0.01). There were significant differences (P < 0.001) in depression, training, and Competition Satisfaction and acceptance variables between the post-test and the measurement three months after the conclusion of the intervention; there were no significant differences in mindfulness and anxiety variables after 7 weeks of training. Practically, athletes with good mental health may perform well; therefore, it is the job of the college administration to assist these athletes in enhancing their comprehension and learning, which could be advantageous to their performance. Athletes can benefit from music therapy to improve their mental health and should be motivated to increase their mental health knowledge. Numerous studies have addressed the mental health concept. However, this study is necessitated by the fact that previous research failed to evaluate the effect of music therapy on the mental health education of athletes.